Successful Management of Pancreatic Ascites with both Conservative Management and Pancreatic Duct Stenting - Kanneganti, Kalyan (Gastroenterology Res, 2009)
Pancreatic ascites is a rare complication and should be suspected in patients with chronic alcoholism and pancreatitis presenting with ascites. The etiology is likely from a pancreatic pseudocyst leakage or due to ductal disruption. Treatment is controversial but includes conservative medical therapy or endoscopic transpapillary pancreatic duct stenting or surgery. We present a case of pancreatic ascites in a patient with alcohol use and chronic pancreatitis. Patient received conservative therapy including octreotide. An endoscopic retrograde cholangiopancreatography was performed, which confirmed a pancreatic duct dehiscence with extravasation of the injected contrast. This was treated with placement of a stent. Patient improved clinically and symptomatically. This case report augments the existing data from two prior reported case series, and this modality of management should be actively pursued in such cases.